Smoking Behaviour in the Home and Incidence ARI symptoms in Cambodia, Timor Leste and Philippines - Allan Sarrita Atchesco; Fernando Sanches; Serlak Sinn Sinn (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The belief that smoking reduces stress, which causes stressed smokers to increase their intensity of smoking, also influences the maintenance of smoking behaviour.This study aimed to determine indoor smoking behavior and ARI symptoms in Cambodia, Timor Leste, and the Philippines. This research uses secondary data, especially DHS data from 2015-2020, in Cambodia, Timor Leste, and the Philippines. This study uses household data with the variables of women's smoking behavior in the home and ARI symptoms in toddlers.The number of times a person smokes per day, week, or month will be given to urban and rural households and recorded. The researcher will compare the number of times a mother smoked in the home with the number of times a child under five had symptoms of ARI. Data analysis was conducted using JAPS software version 16 by conducting frequency distribution and percentage on each variable. Daily smoking at home is highest in Timor Leste (47.5%) compared to daily smoking behavior in the Philippines (47.5%) in urban households. Weekly smoking at home was highest in Timor Leste (11.2%) compared to weekly indoor smoking behavior in the Philippines (7%) in urban households. mothers who smoked in the home had a higher number of children under five with ARI symptoms (Philippines 2.2%, Cambodia 10%) than mothers who did not smoke had a higher number of children under five with ARI symptoms (Philippines 1.5%, Cambodia 5.4%).Mothers' daily smoking behavior in the home is still high in Cambodia, Timor Leste, and the Philippines, especially in rural areas compared to urban areas. Households with mothers who smoke in the home are likelier to have toddlers who experience ARI symptoms than households without mothers who smoke. Cambodia is a country that has a high number of mothers who smoke at home and toddlers who experience ARI symptoms. Keyword: ARI Symptoms, Home, Households, Smoking Behaviour